Digital Creative Team: Collaboration of Potential Actors in the Development of Bowele Marine Tourism Village - Safitri, Reza; Kriyantono, Rachmat; Cahyono, Edi Dwi; Wahyudi, Lestari Eko (Journal of Transformative Governance and Social Justice, 2025)
Malang Regency, particularly its southern region, possesses significant coastal beauty. One prominent example is Purwodadi Village in Tirtoyudo District, recognized as the Bowele Tourism Village, encompassing Bolu-bolu, Wedi Awu, and Lenggoksono beaches. These coastal areas boast pristine natural landscapes, waves suitable for surfing, and rich marine biodiversity, making them premier tourist attractions. Despite its natural potential, the tourism village faces challenges in leveraging digital technology and human resources for tourism promotion. Implementing digital tourism management—such as digital marketing, social media management, and creative content production—remains suboptimal due to the local community's limited knowledge and expertise. A competent digital creative team is essential to foster sustainable tourism development and attract more visitors. This team, collaborating with potential actors, is expected to enhance branding and promotional efforts while producing engaging digital content to increase Bowele's appeal and accessibility. Through the collaboration of village authorities, tourism awareness groups (Pokdarwis), and other key stakeholders, forming a digital creative team is anticipated to optimize the development of Bowele Tourism Village, ultimately providing economic benefits to the local community.